1995
DOI: 10.1007/bf00694745
|View full text |Cite
|
Sign up to set email alerts
|

The Carolina Breast Cancer Study: integrating population-based epidemiology and molecular biology

Abstract: The integration of epidemiology and molecular biology provides a new strategy to identify additional risk factors for breast cancer and to better understand the role played by traditionally recognized risk factors. The Carolina Breast Cancer Study (CBCS) is a population-based, case-control study designed to identify causes of breast cancer among Caucasian and African-American women who are residents of a 24-county area of central and eastern North Carolina. Information on established and potential breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
184
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 199 publications
(188 citation statements)
references
References 35 publications
4
184
0
Order By: Relevance
“…Offset terms were incorporated into the logistic models in order to control for the different ageã nd race-specific sampling fractions utilized for cases and controls (19,21,22). The analysis of breast cancer risk in relation to duration of employment and cumulative indices of exposure was stratified by menopausal status·to evaluate effect measure modification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Offset terms were incorporated into the logistic models in order to control for the different ageã nd race-specific sampling fractions utilized for cases and controls (19,21,22). The analysis of breast cancer risk in relation to duration of employment and cumulative indices of exposure was stratified by menopausal status·to evaluate effect measure modification.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design and identification and characteristics of cases and controls in the first phase of the Carolina Breast Cancer Study (CBCS) have been published in detail elsewhere (19,20) and are briefly described here. The· CBCS is an ongoing population-based case-control study to identify genetic and environmental risk factors .…”
Section: Metiiods Design and Study Populationmentioning
confidence: 99%
“…4 Women aged 20 to 74 years with a first invasive, primary breast cancer diagnosis between May 1993 and May 1996 were eligible; African American case patients and patients younger than 50 years at diagnosis were oversampled to increase the numbers in these subgroups. Sampling fractions and randomized recruitment techniques were used in selecting case patients.56 The same methods were used to sample controls from Division of Motor Vehicle records (if the individuals were younger than 65 years) and Medicare records (if the individuals were 65 years or older); these individuals were frequency matched to the case patient age-race distribution.…”
Section: Methodsmentioning
confidence: 99%
“…The polycyclic aromatic hydrocarbons including benzopyrene in tobacco smoke are mutagenic for the p53 suppressor gene in humans, and 7,12-dimethylbenzanthracene is an inductor of mammary tumors in animals (7). Previous studies showed increased risk of breast cancer for active or passive smokers (8,9).…”
Section: Introductionmentioning
confidence: 99%